Optimism and causal analysis in adventure motorcycling: An investigation of athletes’ resilience - Wulandari, Cahyani; Kristiyanto, Agus; Syaifullah, Rony (UIR Press, 2023)
Resilience in motorcycle adventure activities in each individual requires resilience to face challenges. However, this motorcycle activity has many failures and problems that usually bring up emotions. The purpose of this research was to examine the resilience of community members participating in motor adventure activities. Mixed-methods research was used, with a sequential explanatory research basic design. This study began with quantitative methods and proceeded to qualitative methods. A questionnaire was used to collect quantitative data, while an interview was used to acquire qualitative data. The accumulated interpretation of scores obtained on emotion regulation was 75% (high), impulse control 82% (very high), optimism 84% (very high), causal analysis 82% (very high), empathy 71% (high), self-efficacy 78% (high), and reaching out 87% (very high). This research is limited to the sample used and the scope of research is limited to one area or community. Future research can broaden the scope of research by exploring the factors that influence the resilience of different motorcycle adventure actors, such as psychological, social, and environmental factors. In addition, research can be focused on efforts to increase the resilience of motorcycle adventure actors, such as through training or education programs. The results of this study provide consideration, support, and contribution of ideas to stakeholders to increase the resilience of adventure motorcycle actors in facing challenges in their activities.